Molecular transition of SARS-CoV-2 from critical patients during the first year of the COVID-19 pandemic in Mexico City - De La Cruz-Montoya, Aldo Hugo; Díaz Velásquez, Clara Estela; Martínez-Gregorio, Héctor; Ruiz-De La Cruz, Miguel; Bustos-Arriaga, José; Castro-Jiménez, Tannya Karen; Olguín-Hernández, Jonadab Efraín; Rodríguez-Sosa, Miriam; Terrazas-Valdes, Luis Ignacio; Jiménez-Alvarez, Luis Armando; Regino-Zamarripa, Nora Elemi; Ramírez-Martínez, Gustavo; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: The SARS-CoV-2 virus has caused unprecedented mortality since its emergence in late 2019. The continuous evolution of the viral genome through the concerted action of mutational forces has produced distinct variants that became dominant, challenging human immunity and vaccine development. Aim and methods: In this work, through an integrative genomic approach, we describe the molecular transition of SARS-CoV-2 by analyzing the viral whole genome sequences from 50 critical COVID-19 patients recruited during the first year of the pandemic in Mexico City. Results: Our results revealed differential levels of the evolutionary forces across the genome and specific mutational processes that have shaped the first two epidemiological waves of the pandemic in Mexico. Through phylogenetic analyses, we observed a genomic transition in the circulating SARS-CoV-2 genomes from several lineages prevalent in the first wave to a dominance of the B.1.1.519 variant (defined by T478K, P681H, and T732A mutations in the spike protein) in the second wave. Conclusion: This work contributes to a better understanding of the evolutionary dynamics and selective pressures that act at the genomic level, the prediction of more accurate variants of clinical significance, and a better comprehension of the molecular mechanisms driving the evolution of SARS-CoV-2 to improve vaccine and drug development.